Chemo-physico-mechanical properties of the interface zone between bacterial PLA self-healing capsules and cement paste. (December 2020) - Rodríguez, C. Romero; de Mendonça Filho, F. França; Mercuri, L.; Gan, Y.; Rossi, E.; Anglani, G.; Antonaci, P.; Schlangen, E.; Šavija, B.
Abstract: In this study, the interface between different types of bacteria-embedded self-healing polylactic acid capsules (PLA) and cement paste is investigated. Particularly, the changes in microstructure and mechanical properties of the interface with respect to bulk cement paste were studied. First, nanoindentation was performed to obtain maps of hardness and elastic modulus in the interfaces. Lattice modeling of uniaxial tensile test on the mapped locations was performed then to obtain the overall tensile strength and stiffness of the interface. Moreover, hydrates assemblage and chemical composition around the PLA particles were studied through Backscattering Electron images and Energy Dispersive X-ray Spectroscopy. The ratios between resulting tensile strength and elastic modulus of the interface with respect to bulk paste were obtained for each PLA type. The results suggest that PLA can be tailored to optimize the physico-mechanical properties of the interface and hence, the mechanical behavior and triggering efficiency of the self-healing system.